The Prevalence of Compulsive Buying and Hoarding Behaviours in Emerging, Early, and Middle Adulthood: Multicentre Epidemiological Analysis of Non-clinical Chinese Samples - Ye, Jiawen; Lam, Simon Ching; He, Heping (Frontiers in Psychology, 2021)
Behavioural addictions, such as compulsive buying (CB) and hoarding, are increasingly recognised in the current psychiatric nosology, particularly in developed countries. The prevalence of these disorders may not be static but possibly altered across different age groups. However, studies on this area are rare, and only few have focused on Chinese population. This epidemiological study employs population-based cross-sectional design and collects data in two regions, i.e., Hong Kong and Mainland China. A self-reported questionnaire is constructed based on carefully validated Chinese versions of Richmond Compulsive Buying Scale and Hoarding Rating Scale. A total of 2,439 valid samples are collected and divided into three age groups, i.e., emerging, early and middle adulthood. CB and hoarding behaviours have displayed an inverted u-shaped pattern across the above age groups. In addition, the strength of correlation between the two compulsive behaviours is consistent and maintained across different age groups. These results suggest that the compulsive behaviours vary among different stages of adulthood in developed regions. This newly discovered pattern of compulsive disorders in Chinese population is different from those in American and European populations.